Product diversification and stability of employment and sales: first evidence from German manufacturing firms - Nils Braakmann; Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2009)
We use a unique rich newly built data set for German manufacturing enterprises to investigate the relationship between product diversification and the stability of sales and employment. We find that contrary to portfolio theoretic considerations more diversified firms exhibit a higher variability of sales and employment. However, the effects are negligibly small from an economics point of view.
Keywords: D21; L60; 330; Product diversification; stability; variability; Germany